Regime de ciclos com progressão continuada nas escolas públicas paulistas: um cenário para o estudo dos impactos das mudanças educacionais no capital cultural e habitus dos professores - Souza, Roger Marchesini de Quadros (2005)
The aim of this study is to contribute to the comprehension of how the changes entailed in the educational reform work and are expressed. It was accomplished based on a research about the new set, relative to the scholar organization, created by the changes introduced with the implantation of Cycle Regime with Ongoing Progression at elementary education in public schools from São Paulo. The initial hypothesis was that the this implantation would modify, meaningfully, the school time organization, what would generate a direct impact with the cultural capital and habitus of the teachers. The research took place in 2003 in two public schools from São Paulo state net subordinated to the same Teaching Board. It was made through interviews to two teachers in each school who worked at the second cycle of elementary school, 5th to 8th grades, at a total of four, and to the pedagogic coordinators that were working at this duty since the implantation of the reform. It was also performed the collection and analysis of school documents which expressed the school time organization. This job used the Pierre Bourdieu theoretical corpus as reference, mainly the cultural capital, arbitrary cultural dominant, strategies and habitus, to verify the resulting impact of the reform quoted at the consolidated docent practices. It was testified that the initial hypothesis, concerning the school time, was not proved. Nevertheless, the direct impact on the teacher s cultural capital and habitus regarding to meritocracy, which prizes and settles an ideal student pattern, the pedagogic authority reduction on behalf of ongoing progression that makes impossible the power of the decision about the retention or approval of the pupils, and the valorization and defense of the transmission of scholar contents without which school becomes devoid of its leading duty, was evidenced. Finally the adoption of strategies such as the defense of the Grade Board strengthening and the reduction of the cycles duration from four two years aiming at overcoming these impacts and its effects that are considered damaging, by the docents, to public schools and the pupils future.